Electrospun Cellulose Acetate/Poly(Vinyl Alcohol) Nanofibers Loaded with Methyl Gallate and Gallic Acid for Anti-Staphylococcus aureus Applications - Pimsumon Jiamboonsri; Weradesh Sangkhun; Sompit Wanwong (My University, 2024)
Methyl gallate (MG) and gallic acid (GA) are natural compounds with potent activity against methicillin-resistant
Keywords: Vinyl alcohol; Cellulose acetate; Methyl gallate; Vinyl acetate; Electrospun Nanofibers in Biomedical Applications